A celebration of customs & rituals of the world - Ingpen, Robert R.; Wilkinson, Philip (New York, NY Facts on File, 1996)
Explores initiation rites, wedding feasts, harvest celebrations, religious rituals, and many other customs used around the world to mark all kinds of special occasions.
Includes bibliographical references (p. 219) and index.
Keywords: Manners and customs -- Juvenile literature; Rites and ceremonies -- Juvenile literature; Festivals -- Juvenile literature; Manners and customs; Rites and ceremonies; Festivals